Clinical outcomes associated with catecholamine use in patients diagnosed with Takotsubo cardiomyopathy - Ansari, Uzair; El-Battrawy, Ibrahim; Fastner, Christian; Behnes, Michael; Sattler, Katherine; Huseynov, Aydin; Baumann, Stefan; Tueluemen, Erol; Borggrefe, Martin; Akın, Ibrahim (BMC cardiovascular disorders, 2018)
Recent hypotheses have suggested the pathophysiological role of catecholamines in the evolution of the Takotsubo syndrome (TTS). The extent of cardiac and circulatory compromise dictates the use of some form of supportive therapy. This study was designed to investigate the clinical outcomes associated with catecholamine use in TTS patients.
Gesehen am 07.05.2020